The Mutual Interdependence between Financial Inclusion and Human Development and Their Effects on Economic Development: Comparative Study between Egypt and The BRICS Countries - Helmy, Ashraf (The Arab Journal of Administration, 2024)
This study examines the forward and backward relationships between human development and financial inclusion and their ultimate effects on the process of economic development in Egypt and the BRICS countries. The response of deposits and private credit to domestic savings and the response of private credit to deposits will be used as financial indicators of the status of financial inclusion. Human Development Index and its sub-indices will be used as indicators of the development of human factor. Finally, the state of economic development will be represented here by unemployment, income inequity, and poverty. Panel data and Ordinary Least Squares techniques will be used to analyze annual data from the year 2000 to the year 2018 in the BRICS countries and Egypt. The study found that, in the BRICS countries, there is a mutual interdependence relationship between human development and financial inclusion in the interest of economic development; however, the spread of inequity in education and income may spoil this relationship. In Egypt, thanks to the spread of inequity in education and income, human development and financial inclusion work in two opposite directions, which may result in undesirable repercussions for the state of economic development.